2020
DOI: 10.3390/jcm9103136
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertension with All-Cause Mortality among Hospitalized Patients with COVID-19

Abstract: It is unclear to which extent the higher mortality associated with hypertension in the coronavirus disease (COVID-19) is due to its increased prevalence among older patients or to specific mechanisms. Cross-sectional, observational, retrospective multicenter study, analyzing 12226 patients who required hospital admission in 150 Spanish centers included in the nationwide SEMI-COVID-19 Network. We compared the clinical characteristics of survivors versus non-survivors. The mean age of the study population was 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 27 publications
6
65
1
3
Order By: Relevance
“…Although some differences in baseline characteristics were detected (male gender, older age, and comorbidities were significantly more common among the HD group), appropriate adjustments were performed, concomitant treatments during admission were equally administered, and sensitivity analyses reinforced the robustness of our results. In addition, despite all patients had a severe COVID-19, overall mortality (24.8%) was consistent with that reported from previous studies in the early stages of the pandemics in Europe among hospitalized subjects [38,39], suggesting a lower risk of selection bias.…”
Section: Discussionsupporting
confidence: 90%
“…Although some differences in baseline characteristics were detected (male gender, older age, and comorbidities were significantly more common among the HD group), appropriate adjustments were performed, concomitant treatments during admission were equally administered, and sensitivity analyses reinforced the robustness of our results. In addition, despite all patients had a severe COVID-19, overall mortality (24.8%) was consistent with that reported from previous studies in the early stages of the pandemics in Europe among hospitalized subjects [38,39], suggesting a lower risk of selection bias.…”
Section: Discussionsupporting
confidence: 90%
“…Nine hundred and sixteen potentially relevant studies were screened according to the inclusion and exclusion criteria. Finally, 23 studies with 108,745 COVID-19 patients 1 , 2 , 3 , 4 , 5 , 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were eligibly included in the present quantitative meta-analysis. The study characteristics are summarized in Table 1 .…”
mentioning
confidence: 99%
“…These findings are reassuring, despite the high probability of residual confounding in these analyses. 30 Further support for this interpretation, comes from the Chinese studies we included which reported an additional category of severe SARS-CoV-2-related pneumonia/CoViD-19 (independently of whether patients were admitted to ITU or required ventilation), reflecting local guidelines for the diagnosis and treatment of new coronavirus pneumonia. 31 Some of the Chinese studies showed larger effects, as indicated by Egger’s test.…”
Section: Discussionmentioning
confidence: 96%